Contrast enhancement of CT brain images for detection of ischemic stroke - Tiong-Lang, Tan; Kok-Swee, Sim; Aun-Kee, Chong (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/